Pemberian kombinasi probiotik dan zinc terhadap perubahan kadar hemoglobin, albumin, dan indeks massa tubuh pada pasien tuberkulosis paru - Meika Rahmawati Arifah; Darmono Darmono; Muchlis Achsan Udji Sofro (Jurnal Gizi Klinik Indonesia, 2016)
Background: TB patients are generally the most productive age group and suffer from chronic energy deficiency. Therefore, patients with TB requires a combination of chemotherapy and supplementary feeding as probiotics and zinc to boost the immune response and nutritional status.Objective: To analyze the effect of a combined of probiotics and zinc on the changes of hemoglobin, albumin level, and BMI.Method: This study is a quasi-experimental, randomized design with pre-post test control group involving 52 respondents. They were divided into two groups. The treatment group was given a combination of 1 capsule of probiotics (2 billion probiotics) and zinc 20 mg per day for 28 days. The analysis is paired t-test, independent t-test, Mann-Whitney, Pearson, Spearman, Covariance.Results: There was an increase in hemoglobin (p=0.01), albumin (p=0.01) and BMI (p=0.01). There is no difference between the two groups in the levels of hemoglobin parameter (p=0.21) and BMI (p=0.12), whereas there is a difference parameter albumin levels (p=0.01). The effectiveness of interventions is 4% for hemoglobin levels, 16% to albumin, and 1% for IMT.Conclusion: Probiotics and zinc for 28 days in patients with pulmonary tuberculosis may increase levels of hemoglobin, albumin, and BMI, but there is no significant difference in the changes of BMI. The most powerful influence of intervention effectiveness is on albumin.